The Urgency of Management Functions in Improving the Quality of Education Services in Public Senior High Schools 1 Biak - Hermanu Iriawan; Wilda Sasmita; Muhammad Rusdi (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
The quality of education services is a "fixed price" in realizing the quality of education by the objectives of the Republic of Indonesia. This study aims to determine the importance of management functions in improving the quality of education in the Public Senior High School (SMAN) 1 Biak. A qualitative research approach carried out at Biak 1 High School located in Biak Numfor Regency, West Papua. Data collection techniques are done through observation, interviews, literature study, and documentation. The data analysis technique is done descriptively in compiling information systematically, from existing data so that it is easily understood and interpreted. The results showed that the management functions applied in the Biak Kota 1 High School were: planning, organizing, directing, coordinating, and controlling. In the process seen based on the condition of the school in implementing management functions. These results provide good results from every aspect of the implementation of management functions.